A bioinformatics expert system linking functional data to anatomical outcomes in limb regeneration. Issue 2 (10th July 2014) - Lobo, Daniel; Feldman, Erica B.; Shah, Michelle; Malone, Taylor J.; Levin, Michael
<x xml:space="preserve">Abstract</x> We provide a new formalization of limb regeneration results, and experiments, covering the published data on amphibians, crustaceans, and arthropods. By establishing a free, convenient software expert system matching experiments to their known outcomes, we facilitate model discovery by human scientists and set the stage for the development of artificial intelligence algorithms that help to discover models matching the known facts of regeneration. This is the first step to a bioinformatics of shape – the next generation of computational biology tools for the regeneration community. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>